Recurrent SARS-CoV-2 Omicron broadly neutralizing humanized antibodies in different single human V H 1-2-rearranging mouse models - Himanshu Batra; Sai Luo; Kevin O. Saunders; Jaclyn S. Higgins; Fanchong Jian; Jun Zhang; Md Golam Kibria; G. M. Jonaid; Qingchen J. Zhou; Amanda Eaton; Kenneth Cronin; Michael L. Mallory; et al. (Proceedings of the National Academy of Sciences, 2026)
During V(D)J recombination, antibody diversity is enhanced by nontemplated junctional modifications that generate immensely diverse heavy chain (HC) and light chain (LC) complementarity-determining 3 antigen-contact regions (CDR3s). We previously developed a mouse model that generates diverse antibody repertoires by rearranging a single human V H 1-2 and Vκ1-33, associated with highly diverse CDR3s generated by V(D)J recombination with mouse Ds and/or Js. Immunization of this model with SARS-CoV-2 D614G spike elicited an antibody that potently neutralized SARS-CoV-2 variants through Omicron BA.2.754. Here, we report a related mouse model in which a single V H 1-2 rearranges to human D3-3 and J H 6, generating diverse HC-CDR3s much longer on average than those of our prior model. Omicron BA.4/.5 spike-ferritin nanoparticle-immunization of the new model elicited four highly related humanized antibodies that potently neutralize downstream Omicron subvariants. All four antibodies had 12 AA HC-CDR3s with two aromatic amino acids that engage an epitope comprising a hydrophobic patch opened-up by early Omicron lineage mutations and conserved in subsequent variants. Immunization of our prior, shorter CDR3-based model, elicited slightly less potent neutralizing antibodies that bound the same Omicron epitope, and were similar in all other aspects to those from the long, fully human CDR3 model. One tested antibody from each set reduced lung viral titers in a mouse-adapted BQ1.1 challenge. The antibodies we describe are related in their epitope recognition to recently described antibodies from Omicron-infected humans. These studies validate the utility of single human V H - and Vκ-rearranging mice for discovering humanized antibodies that neutralize emerging pathogens.